Implementation of the Principle of Appropriateness in Determining the Amount of Iddah, Mut'ah, and Child Support for Civil Servants Based on Sema No. 3 of 2018 (Study of Supreme Court Decision Number 42 K/Ag/2024) - Natigor Daulay, R. Fahmi; Muhammad, Ade Sultan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research examines the application of the principle of appropriateness in determining post-divorce maintenance amounts for Civil Servants based on Supreme Court Circular Letter No. 3 of 2018 through a study of Supreme Court Decision Number 42 K/Ag/2024. The regulation of iddah maintenance, mut'ah, and child support in Indonesian positive law has been established in various legal instruments, but its implementation often faces challenges in determining appropriate and fair amounts. Through a normative juridical research method with a case approach, this research analyzes how the Supreme Court applies the principle of appropriateness by considering factors such as the husband's economic capacity as a civil servant, the duration of marriage, the basic needs of the former wife and children, and the principle of a year's living costs as a benchmark for iddah maintenance and mut'ah. This decision becomes an important jurisprudence that corrects lower court decisions by improving the amount of iddah maintenance from Rp7,500,000 to Rp12,000,000, mut'ah from Rp30,000,000 to Rp48,000,000, and child support from Rp2,000,000 to Rp5,000,000 per month with a 10% increase each year, reflecting a progressive approach in religious court practice that prioritizes substantive justice and protection of women's and children's rights after divorce.